PENGUATAN SUPERVISI AKADEMIK DALAM UPAYA PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN SILABUS DAN RPP - Muna, Muna (Gema Pendidikan, 2022)
This study sees that academic supervision activities that are carried out on an ongoing basis can improve teacher competence in compiling syllabus and lesson plans, so that they can assist teachers in developing their abilities to improve the quality of learning. This study aims to analyze the improvement of teacher competence in compiling the syllabus and lesson plans, through ongoing academic supervision activities. This research was conducted at SMA Negeri 1 Sampara, Konawe Regency, Southeast Sulawesi Province. This study used the school action research method, which lasted for two cycles. Collecting data using tests and observations, data were analyzed using percentage analysis. Based on the results of this study, it can be stated that the academic supervision activities carried out on an ongoing basis at SMA Negeri 1 Sampara, Konawe Regency have increased teacher competence in compiling Syllabus and lesson plans. This is evidenced by the number of teachers who deposit the syllabus and lesson plans at the end of the academic supervision activities to 100%. The quality of the syllabus and lesson plans has increased, besides that the teachers have carried out classroom learning according to the plans that have been made previously.